C-Reactive Protein and N-Terminal Pro-brain Natriuretic Peptide Levels Correlate With Impaired Cardiorespiratory Fitness in Patients With Heart Failure Across a Wide Range of Ejection Fraction - van Wezenbeek, Jessie; Canada, Justin M.; Ravindra, Krishna; Carbone, Salvatore; Trankle, Cory R.; Kadariya, Dinesh; Buckley, Leo F.; Del Buono, Marco; Billingsley, Hayley; Viscusi, Michele; Wohlford, George F.; Arena, Ross; et al. (Frontiers in Cardiovascular Medicine, 2018)
Background. Impaired cardiorespiratory fitness (CRF) is a hallmark of heart failure (HF). Serum levels of C-reactive protein (CRP), a systemic inflammatory marker, and of N-terminal pro-brain natriuretic peptide (NT-proBNP), a biomarker of myocardial strain, independently predict adverse outcomes in HF patients. Whether CRP and/or NT-proBNP also predict the degree of CRF impairment in HF patients across a wide range of ejection fraction is not yet established. Methods. Using retrospective analysis, 200 patients with symptomatic HF who completed one or more treadmill cardiopulmonary exercise tests (CPX) using a symptom-limited ramp protocol and had paired measurements of serum high-sensitivity CRP and NT-proBNP on the same day were evaluated. Univariate and multivariate correlations were evaluated with linear regression after logarithmic transformation of CRP (log10) and NT-proBNP (logN). Results. Mean age of patients was 57±10 years and 55% were male. Median CRP levels were 3.7 [1.5-9.0] mg/L, and NT-proBNP levels were 377 [106-1464] pg/ml, respectively. Mean peak oxygen consumption (peak VO2) was 16±4 mlO2•kg-1•min-1. CRP levels significantly correlated with peakVO2 in all patients (R=-0.350, p <0.001) and also separately in the subgroup of patients with reduced left ventricular ejection fraction (LVEF)(HFrEF, N=109)(R=-0.282, p<0.001) and in those with preserved EF (HFpEF, N=57)(R=-0.459, p<0.001). NT-proBNP levels also significantly correlated with peak VO2 in all patients (R=-0.330, p<0.001) and separately in patients with HFrEF (R=-0.342, p<0.001) and HFpEF (R=-0.275, p=0.032). CRP and NT- proBNP did not correlate with each other (R=0.05, p=0.426), but independently predicted peak VO2 (R=0.421, p<0.001 and p<0.001, respectively). Conclusions. Biomarkers of inflammation and myocardial strain independently predict peak VO2 in HF patients. Anti-inflammatory therapies and therapies alleviating myocardial strain may independently improve CRF in HF patients across a large spectrum of LVEF.